A new species of gecko (Squamata: Diplodactylidae: Strophurus) from central Queensland, Australia - Vanderduys, Eric (Zootaxa, 2017)
A new species of diplodactylid gecko in the genus Strophurus Fitzinger, from central Queensland, Australia, is described herein as Strophurus trux sp. nov. It is similar to the recently described Strophurus congoo Vanderduys from north Queensland and apparently shares a habitat preference for Triodia hummock open woodlands. It is notably different from the latter in possessing a vivid yellow to golden eye. It is only known from one small area of the Brigalow Belt Bioregion, although it is expected to occur more widely than the one area in which it has been found. It is likely that it is endemic to the Brigalow Belt Bioregion.